Method for detecting ratio of lithium in lithium-containing mixed material

In the production process of ternary positive electrode materials, a laser particle size tester is used to obtain the particle size volume distribution curve and establish standard equations to quickly detect lithium ratios, which solves the problems of detection time and hysteresis in the existing technology, and achieves fast and accurate lithium ratio detection, avoiding material losses.

CN119643392APending Publication Date: 2025-03-18NANTONG RESHINE NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411914285.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

During the production process of existing ternary positive electrode materials, the ratio detection of the lithium source and the precursor takes a long time, and the detection results are lagging, which makes it difficult to correct the lithium ratio deviation in the batching process in a timely manner, resulting in material losses.

Method used

By preparing standard samples and using laser particle size tester to obtain particle size volume distribution curves, calculate Q/T value, establish a standard equation for the ratio of Q/T value to lithium, and then quickly detect the lithium ratio in the sample to be tested.

Benefits of technology

It realizes rapid and accurate detection of lithium ratio in ternary positive electrode materials, avoids material losses caused by lithium ratio deviation in the batching process, and improves the detection efficiency and accuracy of the production site.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119643392A_ABST
    Figure CN119643392A_ABST
Patent Text Reader

Abstract

The invention discloses a method for detecting the ratio of lithium in a lithium-containing mixed material. The method comprises the following steps: preparing a plurality of standard samples; obtaining a Q / T value corresponding to each standard sample by using the particle size volume distribution curve of each standard sample, Q being a precursor characteristic peak area value, and T being a lithium source characteristic peak area value; performing linear fitting on the Q / T value of each standard sample and the mass ratio to obtain a standard equation; the actual molar ratio N1 of a precursor to a lithium source in a to-be-detected sample is obtained through the standard equation and the particle size and volume distribution curve of the to-be-detected sample, and the to-be-detected sample and the standard sample comprise the precursor and the lithium source which are the same in chemical composition; and judging whether the lithium ratio of the to-be-detected sample is qualified or not according to the actual molar ratio N1. The detection method provided by the invention is short in detection time, rapid detection can be realized on a production site, materials with abnormal lithium ratios can be intercepted in time, and material waste or influence on product quality caused by delayed detection timeliness is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of lithium-ion battery material detection, and in particular to a method for detecting the lithium ratio in a lithium-containing mixed material. Background Art

[0002] Ternary positive electrode materials have relatively high specific energy and working voltage, making them the most commercially promising positive electrode materials at present. In the production process of ternary positive electrode materials, the first step is to mix the ternary precursor with the lithium source to form a dry mix, followed by subsequent sintering, crushing, coating and other processes. Among them, the ratio of lithium source to precursor in the process of forming the dry mix is ​​a key factor affecting performance. If the lithium source is added too little during the actual batching process, the positive electrode material will be deficient in lithium, which will affect the capacity and life of the ternary positive electrode material; if the lithium source is added too much, the residual alkali in the sintered material will be high, resulting in serious gas production at the battery end. Therefore, the accurate ratio of precursor and lithium source in the production process of the ternary positive electrode material batching process is a prerequisite for ensuring stable product quality.

[0003] The current method for detecting the ratio of precursors to lithium sources is to use chemical reagents to titrate the molar amount of metal (Ni, Co, Mn or Al) and the molar amount of lithium in the dry mix. If the ratio of the molar amount of lithium to the total molar amount of metal (Ni, Co, Mn or Al) is within the design range, the lithium ratio in the batching process is considered qualified. However, this method takes a long time to detect and needs to be sent to a special testing room for testing. In the actual production process, the dry mix after batching has been transferred to the kiln for sintering before the test sample is completed. The test results are seriously delayed. Once the lithium ratio in the batching process deviates, it is basically irreparable, resulting in material loss. Summary of the invention

[0004] In view of this, the present application provides a method for detecting the lithium ratio in a lithium-containing mixed material that can solve the above-mentioned technical problems.

[0005] A method for detecting the lithium ratio in a lithium-containing mixed material, comprising: Preparing a plurality of standard samples, each of the standard samples comprising a precursor and a lithium source having a different mass ratio; The Q / T value corresponding to each standard sample is obtained by using the particle size volume distribution curve of each standard sample, wherein the particle size volume distribution curve has a precursor characteristic peak and a lithium source characteristic peak, Q is the area value of the precursor characteristic peak, and T is the area value of the lithium source characteristic peak; the Q / T value of each standard sample is linearly fitted with the mass ratio to obtain a standard equation; Using the standard equation and the particle size volume distribution curve of the sample to be tested, the actual molar ratio N1 of the precursor to the lithium source in the sample to be tested is obtained, wherein the sample to be tested and the standard sample contain the precursor and the lithium source with the same chemical composition; Whether the lithium ratio of the sample to be tested is qualified is judged according to the actual molar ratio N1. In some embodiments, “obtaining the actual molar ratio N1 of the precursor to the lithium source in the sample to be tested by using the standard equation and the particle size volume distribution curve of the sample to be tested” includes: Determine the mass ratio M1 of the precursor to the lithium source in the sample to be tested according to the standard equation using the precursor characteristic peak area value Q1 and the lithium source characteristic peak area value T1 in the particle size volume distribution curve of the sample to be tested; The theoretical mass ratio M0 of the precursor and the lithium source and the theoretical molar ratio N0 of the precursor and the lithium source are obtained, and the actual molar ratio N1 of the precursor and the lithium source in the sample to be tested is calculated according to M0 / M1= N0 / N1.

[0006] In some embodiments, “determining whether the lithium ratio of the sample to be tested is qualified according to the actual molar ratio N1” includes: Compare the actual molar ratio N1 with the theoretical molar ratio N0. If N1 is within the range of N0×(1±1%), the lithium ratio of the sample to be tested is determined to be qualified; if N1 is outside the range of N0×(1±1%), the lithium ratio of the sample to be tested is determined to be unqualified.

[0007] In some embodiments, the standard equation is y=(Q / T)×ka, wherein y is the mass ratio of the precursor to the lithium source in the standard sample, k is the slope, and a is the correction coefficient.

[0008] In some embodiments, the maximum particle size of the precursor in the standard sample is smaller than the minimum particle size of the lithium source in the standard sample, and the maximum particle size of the precursor in the sample to be tested is smaller than the minimum particle size of the lithium source in the sample to be tested.

[0009] In some embodiments, the particle size of the precursor in the standard sample is 0.9 μm to 11.2 μm, and the particle size of the lithium source in the standard sample is 90 μm to 670 μm.

[0010] In some embodiments, the standard sample and the sample to be tested are respectively placed in a solution that does not dissolve the precursor and the lithium source to test the particle size volume distribution.

[0011] In some embodiments, the solution comprises ethanol and / or ethylene glycol.

[0012] In some embodiments, the lithium source includes lithium hydroxide monohydrate, the precursor includes Ni element, Co element and Mn element, or the precursor includes Ni element, Co element and Al element.

[0013] In some embodiments, the particle size volume distribution curve is obtained by a laser particle size tester.

[0014] The present application obtains the particle size volume distribution curve of the precursor and the lithium source of the standard sample, and uses the precursor characteristic peak area value Q and the lithium source characteristic peak area value T in the particle size volume distribution curve to establish a standard equation for the Q / T value and the precursor and lithium source ratio. Based on the standard equation and the particle size volume distribution of the precursor and the lithium source of the sample to be tested, the actual molar ratio N1 of the precursor and the lithium source in the sample to be tested is obtained, and based on the actual molar ratio N1, whether the lithium ratio of the sample to be tested is qualified is judged, thereby achieving the purpose of rapid detection of the lithium source ratio. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 A schematic flow chart of a method for detecting the lithium ratio in a lithium-containing mixed material provided in one embodiment of the present application.

[0016] Figure 2 This is a particle size volume distribution curve of a standard sample in one embodiment of the present application.

[0017] Figure 3 A linear fitting diagram provided for one embodiment of the present application.

[0018] Figure 4 This is a particle size volume distribution curve diagram of the sample to be tested in one embodiment of the present application.

[0019] Figure 5 This is a particle size volume distribution curve of a standard sample in another embodiment of the present application.

[0020] Figure 6 A linear fitting diagram provided for another embodiment of the present application.

[0021] Figure 7 This is a particle size volume distribution curve diagram of the sample to be tested in another embodiment of the present application. DETAILED DESCRIPTION

[0022] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application. The reagents and materials described in the following embodiments can all be obtained from commercial sources.

[0023] See also Figure 1 The present application provides a method for detecting the lithium ratio in a lithium-containing mixed material, comprising: preparing a plurality of standard samples, each standard sample containing a precursor and a lithium source having a different mass ratio; The Q / T value corresponding to each standard sample is obtained by using the particle size volume distribution curve of each standard sample, wherein the particle size volume distribution curve has a precursor characteristic peak and a lithium source characteristic peak, Q is the area value of the precursor characteristic peak, and T is the area value of the lithium source characteristic peak; the Q / T value of each standard sample is linearly fitted with the mass ratio to obtain a standard equation; Using the standard equation and the particle size volume distribution curve of the sample to be tested, the actual molar ratio N1 of the precursor to the lithium source in the sample to be tested is obtained, and the sample to be tested and the standard sample contain the precursor and the lithium source with the same chemical composition; The actual molar ratio N1 is used to determine whether the lithium ratio of the sample to be tested is qualified. In some embodiments, according to the process conditions, the standard mass ratio of the precursor to the lithium source is used as the central value and the standard sample is proportioned within a certain range above and below the central value, which can improve the accuracy of the standard equation obtained by subsequent fitting.

[0024] In some embodiments, the device for testing the particle size volume distribution of the precursor and the lithium source is a laser particle size tester. The laser particle size tester is a commonly used detection device in the production process of ternary positive electrode materials. It can quickly and accurately detect the particle size volume distribution of the material, so that the detection method provided in this application can be used to achieve rapid detection using equipment commonly used in production, and can be detected at the production site without relying on special or rare instruments and equipment. In addition, the same laser particle size tester can be used to detect the particle size volume distribution of the standard sample and the sample to be tested, which can further improve the accuracy of the detection method.

[0025] In some embodiments, “obtaining the actual molar ratio N1 of the precursor to the lithium source in the sample to be tested by using the standard equation and the particle size volume distribution curve of the sample to be tested” includes: Using the precursor characteristic peak area value Q1 and the lithium source characteristic peak area value T1 in the particle size volume distribution curve of the sample to be tested, the mass ratio M1 of the precursor to the lithium source in the sample to be tested is determined according to the standard equation; The theoretical mass ratio M0 of the precursor and the lithium source and the theoretical molar ratio N0 of the precursor and the lithium source are obtained, and the actual molar ratio N1 of the precursor and the lithium source in the sample to be tested is calculated according to M0 / M1= N0 / N1.

[0026] In the present application, "theoretical mass ratio M0 of precursor and lithium source" refers to the mass ratio of the precursor and the lithium source that meet the lithium ratio requirements, "theoretical molar ratio N0 of precursor and lithium source" refers to the ratio of the total molar amount of metal in the precursor that meets the lithium ratio requirements to the molar amount of lithium atoms in the lithium source, and "actual molar ratio N1 of the precursor and the lithium source in the sample to be tested" refers to the ratio of the total molar amount of metal in the precursor to the molar amount of lithium atoms in the lithium source in the sample to be tested.

[0027] Among them, the theoretical mass ratio M0 of the precursor and the lithium source and the theoretical molar ratio N0 of the precursor and the lithium source are obtained according to the process requirements. According to the chemical formula of the ternary positive electrode material Li(NCM)O2, theoretically, the ratio of the theoretical molar amount of Li to the theoretical total molar amount of the metal in the ternary precursor (ie, NCM) is 1:1, but considering the sufficiency of Li burning and reaction during the sintering process, the molar amount of Li should be appropriately excessive. According to the empirical value corresponding to the actual process requirements, the ratio of the theoretical molar amount of Li to the theoretical total molar amount of the metal in the ternary precursor (ie, NCM) is 1.040:1, that is, the theoretical molar ratio N0 of the precursor and the lithium source that meets the ratio requirements is 1:1.04=0.962. Taking the precursor used in the specific embodiment of the present application as an example, the total molar amount of metal in the precursor is measured to be 0.0108 mol / g, the molar mass of lithium hydroxide monohydrate is 0.02384 mol / g, and under the above ratio conditions, the mass of lithium hydroxide monohydrate required for 1000 kg of the precursor is 471 kg. The theoretical mass ratio M0 of the precursor and the lithium source is M0 = 1000 kg / 471 kg = 2.1231.

[0028] In some embodiments, “determining whether the lithium ratio of the sample to be tested is qualified according to the actual molar ratio N1” includes: Compare the actual molar ratio N1 with the theoretical molar ratio N0. If N1 is within the range of N0×(1±1%), the lithium ratio of the sample to be tested is determined to be qualified; if N1 is outside the range of N0×(1±1%), the lithium ratio of the sample to be tested is determined to be unqualified.

[0029] In some embodiments, the standard equation is y=(Q / T)×ka, wherein y is the mass ratio of the precursor and the lithium source in the sample to be tested, Q is the characteristic peak area value of the precursor in the sample to be tested, T is the characteristic peak area value of the lithium source in the sample to be tested, k is the slope of the standard equation, and a is the correction coefficient of the standard equation.

[0030] In some embodiments, the maximum particle size of the precursor in the standard sample is smaller than the minimum particle size of the lithium source in the standard sample, and the maximum particle size of the precursor in the sample to be tested is smaller than the minimum particle size of the lithium source in the sample to be tested. In this way, the test data of the precursor and the lithium source will not interfere with each other, and the detection accuracy of the detection method can be improved.

[0031] In some embodiments, the particle size of the precursor in the standard sample and the sample to be tested is 0.9 μm to 11.2 μm, and the particle size of the lithium source in the standard sample and the sample to be tested is 90 μm to 670 μm. In this way, the particle size range of the precursor and the particle size range of the lithium source can be non-overlapping, thereby improving the accuracy of the detection method.

[0032] In some embodiments, the standard sample and the sample to be tested are placed in a solution in which the precursor and the lithium source are not dissolved, respectively, to test the particle size volume distribution. Placing the standard sample and the sample to be tested in a solution in which the precursor and the lithium source are not dissolved to test the particle size volume distribution can, on the one hand, make the particles in the standard sample and the particles in the sample to be tested evenly dispersed, which is conducive to better detection of the particle size volume distribution; on the other hand, it can reduce the dissolution of the precursor and the lithium source in the solution, thereby improving the accuracy of the detection.

[0033] In some embodiments, the solution that does not dissolve the precursor and the lithium source includes ethanol and / or ethylene glycol. Using ethanol and / or ethylene glycol can achieve the purpose of not dissolving the precursor and the lithium source on the one hand; on the other hand, compared with various acid and alkali solutions, ethanol and ethylene glycol do not produce harmful substances such as waste acid and waste alkali, and are more environmentally friendly.

[0034] In some embodiments, the lithium source includes lithium hydroxide monohydrate, the precursor includes Ni element, Co element, and Mn element, or the precursor includes Ni element, Co element, and Al element.

[0035] In some embodiments, the number of standard samples is greater than or equal to 3. Increasing the number of standard samples is conducive to making the standard equation obtained by fitting closer to reality, and then the conversion coefficient obtained from the standard equation is more accurate, thereby improving the accuracy of detection.

[0036] The present application is described below by specific examples. Those skilled in the art should understand that the preparation methods described in the present application are only examples, and any other suitable preparation methods are within the scope of the present application.

[0037] Example 1 (1) Taking lithium nickel cobalt manganese oxide (LiNCMO2) as an example, a weighing balance with a weighing accuracy of 0.1 mg is used to weigh the precursor and lithium hydroxide monohydrate lithium source according to the ratio shown in Table 1, and then the precursor and lithium hydroxide monohydrate are evenly mixed to prepare a standard sample. Among them, the precursor is composed of a nickel-containing compound, a cobalt-containing compound and a manganese-containing compound. The measured total metal molar mass of nickel, cobalt and manganese in the precursor is 0.0108 mol / g, and the maximum particle size of the precursor is smaller than the minimum particle size of lithium hydroxide monohydrate, that is, the particle size range of the precursor and lithium hydroxide monohydrate does not overlap.

[0038] Table 1 (2) Use a laser particle size tester to test the particle size volume distribution curves of the above three standard samples. The test system is ethylene glycol. That is, each standard sample is dissolved in ethylene glycol and then placed in the laser particle size tester for testing. The particle size volume distribution curves obtained by the test are as follows: Figure 2 shown.

[0039] (3) Use data analysis and processing software to Figure 2 The precursor characteristic peak and lithium source characteristic peak of the particle size volume distribution curve of each standard sample are integrated to obtain the area, and the precursor characteristic peak area value Q and the lithium source characteristic peak area value T are obtained. The standard equation of the linear curve is obtained by fitting the mass ratio of the precursor to the lithium source and the ratio of the characteristic peak area value Q / T. The results are shown in Table 2 and Figure 3 The standard equation obtained by fitting is y=80.158x-0.0066, and the correlation R 2 =0.9997, where y is the mass ratio of the precursor to the lithium source, x is the Q / T ratio, Q is the characteristic peak area value of the precursor, T is the characteristic peak area value of the lithium source, the slope (i.e., the conversion coefficient) is 80.158, and the correction coefficient is -0.0066.

[0040] Table 2 (4) Take the same type of sample as the standard sample (the precursor composition is the same, the lithium source composition is also the same) and take it three times to obtain sample 1, sample 2 and sample 3. Use the same laser particle size tester to test the particle size volume distribution of the above three samples respectively, and obtain Figure 4 The particle size volume distribution curve shown in Figure 2 was used for the data analysis and processing software. Figure 4 The particle size volume distribution curve is used to obtain the area, and the precursor characteristic peak area value Q1 and the lithium source characteristic peak area value T1 of each sample to be tested are obtained. The calculation results are shown in Table 3. The precursor characteristic peak area value Q1 and the lithium source characteristic peak area value T1 of each sample to be tested are substituted into the standard equation y=80.158x-0.0066 to obtain the mass ratio M1 of the precursor to the lithium source of each sample to be tested. The results are shown in Table 3.

[0041] Table 3 For lithium nickel cobalt manganese oxide (LiNCMO2) ternary positive electrode material, the ratio of the theoretical molar amount of Li to the theoretical total molar amount of nickel, cobalt and manganese in NCM is 1:1. Considering the Li burnout and the sufficiency of the reaction during the sintering process, the molar amount of Li should be appropriately excessive. Accordingly, according to the empirical value corresponding to the actual process requirements, the ratio of the molar amount of lithium in the lithium hydroxide monohydrate lithium source to the total molar amount of metal elements in the ternary precursor is usually taken as 1.040, that is, the theoretical ratio N0 of the total molar amount of metal elements in the precursor and the molar amount of lithium in the lithium source should be 1:1.040=0.962.

[0042] The total molar mass of the metal in the precursor used in this embodiment is measured to be 0.0108 mol / g, and the molar mass of lithium hydroxide monohydrate is 0.02384 mol / g. Correspondingly, the total molar mass of the metal in 1000 kg of the ternary precursor is 10.8×103 mol, according to the above principle, the lithium source is in an appropriate excess of 1.040, and the molar amount of lithium hydroxide monohydrate required is 11.232×10 3 mol. According to the molar mass of lithium hydroxide monohydrate of 0.02384 mol / g, 471kg of lithium hydroxide monohydrate lithium source is required, so the theoretical mass ratio M0 of the precursor to the lithium source is 1000:471=2.1231. According to the actual mass ratio M1 of the precursor to the lithium source in the sample to be tested of 2.1173, according to M0 / M1=N0 / N1, the actual molar ratio N1 of the total molar amount of metal in the precursor to the molar amount of lithium in lithium hydroxide monohydrate in the corresponding sample to be tested is 0.959.

[0043] According to the process requirements, if the actual molar ratio N1 is within the range of (1±1%) N0, the lithium ratio can be considered qualified; if the actual molar ratio N1 is not within the range of (1±1%) N0, the lithium ratio of the sample to be tested is judged to be unqualified. Taking the theoretical molar ratio N0=0.962 as an example, the actual molar ratio N1 is qualified between 0.952~0.972.

[0044] According to the above calculation results, the actual molar ratio N1 (N1=0.959) is close to the theoretical molar ratio N0 (N0=0.962), and falls within the qualified range of 0.952~0.972. Therefore, the deviation between the actual molar ratio and the theoretical molar ratio can meet the requirements of the ternary positive electrode material batching process.

[0045] The detection method of the present application can be combined with a laser particle size tester and data processing software to quickly obtain the test results. The test time for a single sample is short, and the test can be completed and the test results can be obtained within 10 minutes, which will not affect the normal flow of materials on the production line.

[0046] Example 2 (1) Taking lithium nickel cobalt manganese oxide (LiNCMO2) as an example, a weighing balance with a weighing accuracy of 0.1 mg is used to weigh the precursor and lithium hydroxide monohydrate source with overlapping particle size distribution according to the ratio shown in Table 4, and then the precursor and the lithium hydroxide monohydrate source are evenly mixed to prepare a standard sample. The precursor in this step has the same components and composition as the precursor in step (1) of Example 1, and the lithium hydroxide monohydrate source has the same components and composition as the lithium hydroxide monohydrate source in step (1) of Example 1. The difference between the precursor and the lithium hydroxide monohydrate source selected in this step and step (1) of Example 1 is only that the particle size range is different. The particle size distribution range of the lithium hydroxide monohydrate source in this step partially overlaps with the particle size distribution range of the precursor.

[0047] Table 4 (2) The particle size volume distribution curves of the three standard samples in Table 4 were tested using the same laser particle size tester as in Example 1. The test system was ethylene glycol. That is, each standard sample was dissolved in ethylene glycol and then placed in the laser particle size tester for testing. The particle size volume distribution curves obtained by the test are shown in FIG. Figure 5 shown.

[0048] (3) Use data analysis and processing software to Figure 5 The precursor characteristic peak and monohydrate lithium hydroxide lithium source characteristic peak of the particle size volume distribution curve of each standard sample are integrated to obtain the area, and the precursor characteristic peak area value Q and the monohydrate lithium hydroxide lithium source characteristic peak area value T are obtained. The mass ratio of the precursor to the lithium source and the ratio of the characteristic peak area Q / T are fitted to obtain the standard equation of the linear curve. The results are shown in Table 5 and Figure 6 The standard equation obtained by fitting is y=6.2041x-0.3571, and the correlation R 2 =0.9998, where y is the mass ratio of the precursor to the lithium source, x is the Q / T ratio, Q is the characteristic peak area value of the precursor, T is the characteristic peak area value of the lithium source, the slope (i.e., the conversion coefficient) is 6.2041, and the correction coefficient is -0.3571.

[0049] Table 5 (4) Take the same type of sample as the standard sample (the precursor composition is the same, the lithium source composition is also the same) and take it three times to obtain sample 1, sample 2 and sample 3. Use the same laser particle size tester to test the particle size volume distribution of the above three samples respectively, and obtain Figure 7 The particle size volume distribution curve shown in Figure 2 was used for the data analysis and processing software. Figure 7 The particle size volume distribution curve is used to obtain the area, and the precursor characteristic peak area value Q1 and the lithium source characteristic peak area value T1 of each sample to be tested are obtained. The calculation results are shown in Table 6. The precursor characteristic peak area value Q1 and the lithium source characteristic peak area value T1 of each sample to be tested are substituted into the standard equation y=6.2041x-0.3571 to obtain the mass ratio M1 of the precursor to the lithium source of each sample to be tested. The results are shown in Table 6.

[0050] Table 6 The same reasoning process as in Example 1, the theoretical mass ratio M0 of the precursor to the lithium source in this embodiment is 1000:471=2.1231, and the theoretical molar ratio N0 of the precursor to the lithium source is 0.962. According to the actual mass ratio M1 of the precursor to the lithium source in the sample to be tested, which is 1.7295, and according to M0 / M1=N0 / N1, it is calculated that in the sample to be tested, the ratio N1 of the total molar amount of the metal elements in the ternary precursor to the molar amount of lithium in the lithium hydroxide monohydrate lithium source is 0.784.

[0051] According to the above calculation results, the actual molar ratio N1 deviates greatly from the theoretical molar ratio N0, and the actual molar ratio N1 is not within the qualified range of 0.952~0.972. This is mainly because the particle size volume distributions of the precursor and the lithium source in Example 2 overlap, resulting in an offset between the integral areas of the characteristic peaks of the two materials and the actual true values, causing distortion of the test results.

[0052] Therefore, compared with the overlapping area of ​​the particle size volume distribution of the precursor and the lithium source, the particle size volume distribution of the precursor and the lithium source has no overlapping area, that is, the maximum particle size of the precursor is smaller than the minimum particle size of the lithium source. The test results obtained according to the detection method provided in this application are more accurate.

[0053] In summary, the method for detecting the lithium ratio in the lithium-containing mixed material provided in the present application has the following advantages: (1) It can be quickly tested at the production site, with a short testing time and measurement accuracy that meets the process requirements. The testing time does not affect the material flow during the continuous production process. When it is found that the ratio does not meet the process requirements, there is an opportunity to remedy the situation on site, avoiding material loss and affecting product quality.

[0054] (2) The laser particle size tester can be integrated with the data processing software to obtain the detection results of the precursor and lithium source ratio, further improving the timeliness and accuracy of the detection.

[0055] (3) It can be extended to other types of powder materials and granular materials for proportion testing, with specific scalability and universal applicability.

[0056] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application is described in detail with reference to the above implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.

Claims

1. A method for detecting the lithium ratio in a lithium-containing mixed material, characterized in that: include: Preparing a plurality of standard samples, each of the standard samples comprising a precursor and a lithium source having a different mass ratio; The Q / T value corresponding to each standard sample is obtained by using the particle size volume distribution curve of each standard sample, wherein the particle size volume distribution curve has a precursor characteristic peak and a lithium source characteristic peak, Q is the area value of the precursor characteristic peak, and T is the area value of the lithium source characteristic peak; the Q / T value of each standard sample is linearly fitted with the mass ratio to obtain a standard equation; Using the standard equation and the particle size volume distribution curve of the sample to be tested, the actual molar ratio N1 of the precursor to the lithium source in the sample to be tested is obtained, wherein the sample to be tested and the standard sample contain the precursor and the lithium source with the same chemical composition; Whether the lithium ratio of the sample to be tested is qualified is judged according to the actual molar ratio N1.

2. The method for detecting the lithium ratio in the lithium-containing mixed material according to claim 1, characterized in that: “Using the standard equation and the particle size volume distribution curve of the sample to be tested to obtain the actual molar ratio N1 of the precursor to the lithium source in the sample to be tested” includes: Determine the mass ratio M1 of the precursor to the lithium source in the sample to be tested according to the standard equation using the precursor characteristic peak area value Q1 and the lithium source characteristic peak area value T1 in the particle size volume distribution curve of the sample to be tested; The theoretical mass ratio M0 of the precursor and the lithium source and the theoretical molar ratio N0 of the precursor and the lithium source are obtained, and the actual molar ratio N1 of the precursor and the lithium source in the sample to be tested is calculated according to M0 / M1=N0 / N1.

3. The method for detecting the lithium ratio in the lithium-containing mixed material according to claim 2, characterized in that: "Judging whether the lithium ratio of the sample to be tested is qualified according to the actual molar ratio N1" includes: Compare the actual molar ratio N1 with the theoretical molar ratio N0. If N1 is within the range of N0×(1±1%), the lithium ratio of the sample to be tested is determined to be qualified; if N1 is outside the range of N0×(1±1%), the lithium ratio of the sample to be tested is determined to be unqualified.

4. The method for detecting the lithium ratio in the lithium-containing mixed material according to claim 1, characterized in that: The standard equation is y=(Q / T)×ka, wherein y is the mass ratio of the precursor to the lithium source in the standard sample, k is the slope, and a is the correction coefficient.

5. The method for detecting the lithium ratio in the lithium-containing mixed material according to claim 1, characterized in that: The maximum particle size of the precursor in the standard sample is smaller than the minimum particle size of the lithium source in the standard sample, and the maximum particle size of the precursor in the sample to be tested is smaller than the minimum particle size of the lithium source in the sample to be tested.

6. The method for detecting the lithium ratio in the lithium-containing mixed material according to claim 1, characterized in that: The particle size of the precursor in the standard sample is 0.9 μm to 11.2 μm, and the particle size of the lithium source in the standard sample is 90 μm to 670 μm.

7. The method for detecting the lithium ratio in the lithium-containing mixed material according to claim 1, characterized in that: The standard sample and the sample to be tested are respectively placed in a solution that does not dissolve the precursor and the lithium source to test the particle size volume distribution.

8. The method for detecting the lithium ratio in the lithium-containing mixed material according to claim 7, characterized in that: The solution includes ethanol and / or ethylene glycol.

9. The method for detecting the lithium ratio in the lithium-containing mixed material according to claim 1, characterized in that: The lithium source includes lithium hydroxide monohydrate, the precursor includes Ni element, Co element and Mn element, or the precursor includes Ni element, Co element and Al element.

10. The method for detecting the lithium ratio in the lithium-containing mixed material according to claim 1, characterized in that: The particle size volume distribution curve is obtained by a laser particle size tester.